Zwitterionic poly(sulfobetaine methacrylate)-based hydrogel coating for drinking water distribution systems to inhibit adhesion of waterborne bacteria - Sójka, Olga; van der Mei, Henny C.; van Rijn, Patrick; Gagliano, Maria Cristina (Frontiers in Bioengineering and Biotechnology, 2023)
Presence of biofilms in drinking water distribution systems (DWDS) can be a nuisance, leading to several operational and maintenance issues (i.e. increased secondary disinfectants demand, pipe damage or increased flow resistance), and so far, no single control practice was found to be sufficiently effective. Here, we propose poly(sulfobetaine methacrylate) (P(SBMA))-based hydrogel coating application as a biofilm control strategy in DWDS. The P(SBMA) coating was synthetized through photoinitiated free radical polymerization on polydimethylsiloxane with different combinations of SBMA as a monomer, and N,N’-methylenebis(acrylamide) (BIS) as a cross-linker. The most stable coating in terms of its mechanical properties was obtained using 20% SBMA with a 20:1 SBMA:BIS ratio. The coating was characterized using Scanning Electron Microscopy, Energy Dispersive X-Ray Spectroscopy, and water contact angle measurements. The anti-adhesive performance of the coating was evaluated in a parallel-plate flow chamber system against adhesion of four bacterial strains representing genera commonly identified in DWDS biofilm communities, Sphingomonas and Pseudomonas. The selected strains exhibited varying adhesion behaviors in terms of attachment density and bacteria distribution on the surface. Despite these differences, after 4 h, presence of the P(SBMA)-based hydrogel coating significantly reduced the number of adhering bacteria by 97%, 93%, 98% and 99%, for Sphingomonas Sph5, Sphingomonas Sph10, Pseudomonas extremorientalis and Pseudomonas aeruginosa, respectively, compared to non-coated surfaces. These findings motivate further research into a potential application of a hydrogel antiadhesive coating as a localized biofilm control strategy in DWDS, especially on materials known to promote excessive biofilm growth.